MOTHERS KNOWLEDGE TOWARDS WOUND CARE IN THE GREATER BANDUNG AREA - OKTAVIANI, DEDE JIHAN; ZUHROTUN, ADE; BARKAH, CECEP SAFA'ATUL (International Journal of Applied Pharmaceutics, 2023)
Objective: Proper wound care is essential to prevent complications and worsening of the injured patient. Everyone in the family needs to possess wound care knowledge, especially the mother, who plays a role in making decisions about health care and family health behaviors. This study aims to evaluate mothers' knowledge towards wound care in the Greater Bandung Area. Methods: This cross-sectional study involved 100 participants with varied backgrounds and had met the inclusion criteria. The study was conducted using questionnaires distributed online to the mother community living in the Greater Bandung Area, West Java, then data processing and analysis were carried out. Results: The results showed that mothers in the Greater Bandung Area had a good level of knowledge (27%), average (52%), and less (21%). In addition, plasters with wound care solutions were still the mothers' main choice in wound care. Nevertheless, there are many choices of pharmaceutical dosage forms for wound care that have been developed today to optimize the wound healing process. Conclusion: Most of the mothers already have an average level of knowledge to good. However, there are still quite a lot of mothers who have a lack of knowledge related to wound care. Therefore, educational programs must be developed to raise awareness about wound care and management, as well as knowledge about pharmaceutical dosage forms for wound care.